(3JaSjQ GdbQBf GdcQjes - (3nepqcj Hf CHj WGdH nMoqehT Hf eMeO Hf eNJGQ GdCfOdSj GdbjSj, CHh eMeO,J (B437 (3g` s
(3ChdgG (B:s
(3jHOC CKfGA JaSjQ bhdg JYGdi (B" (3hMhQ Yjf cCeKGd GddDdD Gdecfhf (B" (3ai ShQI GdhGbYI s
(3BNQgG (B:s
(3jfJgi HBNQ GdbQBf s
(3HgG CKGQ WeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B286 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B3s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs